Gender in Psychotherapy: How Does the Literature Portray the Power Dynamics in a Female Therapist-male Client Dyad? - Dumitrache, Adina (Auckland University of Technology, 2016)
This dissertation aimed to reveal and explore how the reviewed literature portrayed the gendered power dynamics that may play out in a psychotherapeutic alliance between a female therapist and a male client. This research offers an investigation of the literature on male gender roles socialisation, and how men's distinctive ways of communicating their emotions may influence their attitudes towards therapy, and towards female therapists in particular. It also offers an understanding of the concept of power and how the inherent power differential in psychotherapy may contribute to the imbalance of power between female therapists and male clients. Alternatively, the study explores the transference and countertransference phenomena that may emerge in the female therapist-male client dyad. The data was examined from the perspective of female therapists working with male clients. Finally, the purpose of this research is to support the psychotherapy practice and training by offering an understanding of the gendered power dynamics that may occur in a female therapist-male client dyad.
Keywords: Gender; Female therapist; Male clients; Maternal transference; Paternal transference; Sexual feelings; Power dynamics; Erotic transference; Psychotherapy practice; Psychotherapy training; Gender socialisation; Male aggression in psychotherapy